2013
DOI: 10.1179/1973947812y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant and adjuvant chemotherapy with high-dose ifosfamide, doxorubicin, cisplatin and high-dose methotrexate in non-metastatic osteosarcoma of the extremities: a phase II trial in Japan

Abstract: From 1997 to 2003, 40 patients (all <40 years of age) with non-metastatic osteosarcoma of the extremities were treated with OOS-D and definitive surgery. Two cycles of doxorubicin 90 mg/m(2) plus cisplatin 120 mg/m(2) and ifosfamide 15 g/m(2) were given as neoadjuvant chemotherapy, and two cycles of doxorubicin/cisplatin and ifosfamide, and two cycles of high-dose methotrexate (10-12 g/m(2)) were given post-operatively. All patients underwent limb salvage surgeries, and 66% showed good response to neoadjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Generally, it is considered an aggressive malignancy that arises from mesenchymal origin which exhibits osteoblastic differentiation and produces malignant osteoid matrix (2). The 10-year overall survival rate has improved to ~65% attributed to neoadjuvant chemotherapy and improved surgical techniques which nevertheless remains essentially unchanged during the past two decades (3,4). However, 10-year survival rates continue to be unsatisfactory for patients with metastatic and recurrent disease, respectively, 25% (5) and <20% (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is considered an aggressive malignancy that arises from mesenchymal origin which exhibits osteoblastic differentiation and produces malignant osteoid matrix (2). The 10-year overall survival rate has improved to ~65% attributed to neoadjuvant chemotherapy and improved surgical techniques which nevertheless remains essentially unchanged during the past two decades (3,4). However, 10-year survival rates continue to be unsatisfactory for patients with metastatic and recurrent disease, respectively, 25% (5) and <20% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Sinomenine (C 19 H 23 NO 4 , Fig. 1A), an alkaloid isolated from the Chinese medicinal herb, has been successfully utilized to treat rheumatoid arthritis for centuries (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ifosfamide containing combination therapy in recurrent or refractory osteosarcoma has not bee well defined, and the results differed very much. The response rate of Zhao et al was (Harris et al, 1995;Basaran et al, 2007;Zhao et al, 2010;Kudawara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggested that a more prolonged infusion may have an improved cytotoxicity and tolerability profile although it is associated with worse urothelial toxicity compared with the three day infusion (Lorigan et al, 2007). There is clinical investigation for the use of ifosfamide in combination with other chemotherapeutic agents, eg., cisplatin, epirubicin , methotrexate etc (Harris et al, 1995;Basaran et al, 2007;Zhao et al, 2010;Kudawara et al, 2013). However, the role of ifosfamide containing combination therapy in recurrent or refractory osteosarcoma has not bee well defined, and the results differed very much.…”
Section: Introductionmentioning
confidence: 99%
“…But 80-90% of patients treated with only surgery develop metastasis. With the use of preoperative and postoperative chemotherapy it is possible to achive cure in two-thirds of patients (Kudawara et al, 2013). In metastatic patients the choice of treatment is chemotherapy.…”
Section: Introductionmentioning
confidence: 99%